The Role of SCM Capabilities to Support Automotive Industry Trends - Luiz Felipe Scavarda (Brazilian Journal of Operations & Production Management, 2010)
As Supply Chain Management (SCM) becomes essential to generate competitive advantage, the development of capabilities in cooperation with other supply chain members is a premise for success. The goal of this paper is to analyze the role these SCM capabilities play in automotive industry supply chains. The paper offers first a study based in the literature and in interviews regarding trends in the automotive industry, SCM capabilities and their co-relation, which resulted in a formal definition for SCM capability. Then a case study in a European Vehicle Manufacturer is presented and discussed. The case study was conducted with three supply chains embracing, among other significant members, 3 vehicle plants and 2 supplier parks located in Western Europe and in South Africa. Within the case study, we analyze how the SCM capabilities are related to the vehicle manufacturer strategic goals and correlate the trends with the capabilities developed within the three supply chains. The analysis allowed us to conclude that the SCM capabilities identified by the study constitute a response to support trends in the automotive industry, as they intend to bring advantages that obey a new logic in competition based on chains. As a spin off of the research, it was also possible to identify that SCM is still limited to the immediate chain of vehicle manufacturers.